Research progress on aroma-enhancing effect of glutathione in fruit wine brewing - ZHAI Junjun, WANG Xiaoyu, WANG Fei, ZHAO Wanrong, XUE Jia, ZHANG Fangfang, ZHAO Pengtao (Zhongguo niangzao)
The antioxidant properties of glutathione significantly affect the formation of aroma during the fruit wine fermentation process, and it is also a precursor to the synthesis of mercaptan aroma compounds, which can be used as an essential substance for modulating and enhancing the aroma of fruit wine. The dual roles of glutathione as a "substrate" and "enzyme-promoted" agent during the aroma-enhancing fermentation process of fruit wine were reviewed, and the protective and regulatory mechanisms of glutathione on key aroma components in fruit wine were reviewed. Furthermore, the positive effects of Saccharomyces cerevisiae, non-Saccharomyces cerevisiae, glutathione-enriched inactive dry yeast and live yeast cell derivative on aroma compounds under the regulation of glutathione were discussed, aiming to provide a theoretical basis and reference for further research on enhancing the aroma of fruit wine with glutathione.